Investigating the Structure of Neurotoxic Protein Aggregates Inside Cells - Bäuerlein, Felix J.B.; Fernández-Busnadiego, Rubén; Baumeister, Wolfgang (Trends in cell biology, 2020)
Neurodegenerative diseases affect the lives of millions of people across the world, being particularly prevalent in the aging population. Despite huge research efforts, conclusive insights into the disease mechanisms are still lacking. Therefore, therapeutic strategies are limited to symptomatic treatments. A common histopathological hallmark of many neurodegenerative diseases is the presence of large pathognomonic protein aggregates, but their role in the disease pathology is unclear and subject to controversy. Here, we discuss imaging methods allowing investigation of these structures within their cellular environment: conventional electron microscopy (EM), super-resolution light microscopy (SR-LM), and cryo-electron tomography (cryo-ET). Multidisciplinary approaches are key for understanding neurodegenerative diseases and may contribute to the development of effective treatments. For simplicity, we focus on huntingtin aggregates, characteristic of Huntington’s disease. Despite massive research efforts, conclusive insights into the pathomechanisms of neurodegenerative diseases are lacking.A histopathological hallmark of neurodegenerative diseases are large protein aggregates (inclusion bodies). Their role in the disease pathology is unclear.Methods with subcellular resolution (cryo-electron tomography, super-resolution light microscopy, and conventional electron microscopy) are invaluable to investigate the involvement of inclusion bodies in neurodegeneration.The investigation of vital patient-derived material with those high-resolution techniques holds high potential for major breakthroughs in understanding neurodegenerative diseases and will may contribute to the development of effective treatments.